2018
DOI: 10.1212/wnl.0000000000005680
|View full text |Cite|
|
Sign up to set email alerts
|

Eteplirsen treatment for Duchenne muscular dystrophy

Abstract: This study provides Class II evidence of the muscle cell penetration, exon skipping, and induction of novel dystrophin expression by eteplirsen, as confirmed by 4 assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
152
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(157 citation statements)
references
References 34 publications
2
152
1
2
Order By: Relevance
“…To our knowledge, this is the longest period of exposure reported to an investigational drug in DMD outside that of GC use. Previously the longest follow-up time was 188 weeks (3.6 years) in drisapersen treated patients [23] and 180 weeks (3.5 years) in eteplirsen treated patients [24] ; with 12 subjects followed-up in both studies.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the longest period of exposure reported to an investigational drug in DMD outside that of GC use. Previously the longest follow-up time was 188 weeks (3.6 years) in drisapersen treated patients [23] and 180 weeks (3.5 years) in eteplirsen treated patients [24] ; with 12 subjects followed-up in both studies.…”
Section: Discussionmentioning
confidence: 99%
“…This makes accurate quantification of dystrophin produced as a result of therapeutic intervention challenging via current conventional methods. This challenge is further compounded by the very low and variable expression of induced dystrophin that has been observed in recent trials involving antisense oligonucleotides [13,14,17,25,26,46] coupled with the observation that most DMD patient samples also have low level residual dystrophin expression at baseline, highlighting the necessity for a highly sensitive detection method capable of detecting dystrophin signal over a wide dynamic range to resolve even subtle differences between pre-and posttreatment biopsies [3]. The amount and distribution pattern of induced dystrophin needed for functional benefit in humans is not yet known although it is suggested that levels as low as 30% could be sufficient to completely avoid muscle weakness [33], while lower levels are expected to reduce the rate of muscle damage.…”
Section: Discussionmentioning
confidence: 99%
“…Eteplirsen increased muscle dystrophin after 180 weeks of use in 11 treated DMD patients, compared with 13 controls. Dystrophin increased 100% when measured by real-time PCR techniques, 11.6 times by Western blot techniques (p < 0.007) and 7.4 to 15.5 times by immunohistochemistry (p < 0.001) 63 .…”
Section: Eteplirsenmentioning
confidence: 95%